En ny metod för intraoral röntgenundersökning på häst - Lindecrantz, Kajsa (SLU/Dept. of Clinical Sciences (until 231231), 2007)
A method for equine intra oral radiology has been tested. In the study, both a digital system with an intraoral sensor connected to a laptop and a system utilizing image plates and digital developing was tested, initially on cadaver sculls and finally on sedated horses.